Cognitive Behaviour Therapy for Reducing Anxiety in School- Aged Children Diagnosed with Autism Spectrum Disorders - Kirstin Tait (New Zealand Journal of Teachers' Work)
I conducted a systematic review to identify studies that examined the effectiveness of cognitive behavioural therapy (CBT) in reducing clinical levels of anxiety in school-age children identified with autism spectrum disorders (ASD). This is an important consideration for teachers given the prevalence of children with an ASD diagnosis and high comorbidity of ASD and clinical anxiety. Anxiety symptoms can cause distress to children, peers, parents and teachers, and be detrimental to academic and social performance. CBT is a skill building approach which aims to change maladaptive thought and behaviour patterns. Of the 16 studies reviewed, 14 indicated a reduction in parent, teacher, and clinician identified anxiety symptoms in children with ASD who participated in CBT programs. While this indicates a high level of effectiveness, caution must be applied in interpreting self-reported anxiety symptoms as 6 of the 16 studies showed no significant improvement on self-report scales. Teacher expertise is therefore paramount in understanding the complexities of ASD, in making evidence-based decisions, and in interpreting the effectiveness of interventions from the child’s perspective.